Assessing Impact of Vegetable Extension in Mid-hills of Uttarakhand - Singh, S.R.K.; Srinivas, K.; Singh, K.P.; Gautam, U.S.; Dixit, A.K. (Indian Journal of Extension Education, 2009)
Uttaranchal hills have been recognized as a hub for off-season vegetables. However, the growers are unable to harness the potential benefits of vegetable cultivation due to lack of improved production technologies, poor access to market and inadequate extension support. To overcome this, extension interventions including market-led extension (MLE) approach were carried out in four villages, situated in mid-hills in Uttarakhand. A total of 150 farmers from six villages (four were adopted and two were non-adopted), 25 from each village, were selected and interviewed personally. After three years, impact data revealed that interventions resulted in increased yields of tomato (116.3 to 186.9 q/ha), capsicum (80.0 to 118.6 q/ha), French bean (54.3 to 83.1 q/ ha), pea (65.3 to 89.2 q/ha). As a result, the income of the adopted farmers increased by 29 -74 percent over existing technology and market strategies practiced by the non-adopted farmers. Results shown that interventions were highly effective and increased awareness about the recent technology (from 32 to 89 %), Visits per month (1 to 8), field days per trimester (0 to 1), linkage (1.0 to 6.5), farmers training/year (1 to 6). Regarding extension efficiency, all three selected indicators showed significant changes, viz., Performance Index (47 to 92%), Penetration index (43 to 71%), and Achievement Index (40 to 66 %).